Analisis Pengaruh Kualitas dan Kepercayaan Orang Tua/Wali Murid dalam Memilih Sekolah Menengah Pertama Islam untuk Putra-Putrinya (Studi pada SMP Islam Al-Azhar 12 Rawamangun) - Zainal, Arnoldi (Jurnal Aplikasi Manajemen, 2013)
The purpose of this research is to analyze the influence of the quality and trust of parents /guardians in choosing islamic secondary school for their children. Test used for the study variables usingValidity, reliability testing and test classical assumption is normality test, multicollinearity andheterocedastisity.Hypothesis test using linear regression analysis. Based on the research above it can beargued that the quality variable and the trust variables together influence the decision of parents inchoosing a school. However, based on research partially, school quality variables do not significantlyinfluence the decisions of parents in choosing schools. The variables were significant and dominant influenceon the decision of parents to choose schools is trust variable.